Inisiatif Kolaboratif Pembangunan Rumah Pupuk untuk Meningkatkan Produktivitas Pertanian di Desa Jatimulyo - Didit Gunawan Prasetyo Jati; Andrew Gabriel Mamengko (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
This community engagement program revitalizes agricultural infrastructure in Jatimulyo Village, Yogyakarta, through the construction of a new fertilizer storage facility. The main issue was the severe degradation of the previous building caused by decay and termite infestation. Its location on a steep slope further obstructed logistics and access, disrupting fertilizer storage and negatively affecting agricultural productivity. The solution was carried out through collaboration among the Bakti Anubawa Community Engagement Program Committee of Atma Jaya Yogyakarta University (UAJY), KWT Amanah, the village government, and the local community. The program followed systematic stages: field observation, outreach focused on planning and construction standards for sloped terrain, and physical implementation. A key improvement was replacing the deteriorated wooden structure with reinforced concrete for better durability and slope stability. Technical specifications included 300×300 mm river stone foundations, 4D8 main reinforcement with D6-200 stirrups for beams and columns, a 10 cm floor slab, and a ventilated galvalum roof for proper air circulation. Program outputs include detailed working drawings, a transparent budget plan (RAB), and a functional fertilizer storage building that supports efficient logistics, protects fertilizer quality, and improves agricultural productivity and community welfare. This project reflects sustainable implementation of the Tri Dharma Perguruan Tinggi.